Autograph letter signed from Ignaz Moscheles to Wilhelmine Schröder Devrient - Moscheles, Ignaz, 1794-1870:::Creator::::::::::::; Schröder-Devrient, Wilhelmine, 1804-1860:::Contributor:::::::::::: (2021)
Autograph letter signed from Ignaz Moscheles to Wilhelmine Schröder Devrient, sent from 3 Chester Place, Regents Park, London, dated May 19, 1832, praising her debut performance as Leonore in Fidelio.